Are the People of West Java Ready to Face the Covid-19 Pandemic? Study of Psychological Capital and Learning Agility - Nugraha, Yus; Yanuarti, Nurul; Hami, Azhar El (Journal of Psychological Science and Profession, 2024)
Designing policies to prepare a resilient society to face sudden downturns is very important for the government, for example, when society faces the impact of the Covid-19 pandemic. In this case, the principal capitals that the community must rely on are their psychological readiness and also their ability to learn quickly in difficult situations. These principle capitals are then called psychological capital and learning agility. West Java is one of the provinces that contributes to the country's economy strategically; in this case, it is necessary to always pay attention to the readiness of its people, especially in certain professions that have been directly affected by the difficult situation during the Covid-19 pandemic. This research was conducted on 215 participants who were laborers, online motorcycle-taxi drivers, microbusiness owners, and teachers using an incidental sampling method. The results show that people in West Java with these four professions have psychological capital that makes them psychologically ready to face challenges in difficult situations (Covid-19 pandemic) and have the willingness to learn and master new competencies quickly. These traits support them in overcoming the challenges that suddenly came during the Covid-19 pandemic.